Cutaneous squamous cell carcinoma: an epidemiological review. (1st August 2017) - Green, A.C.; Olsen, C.M.
Summary: Cutaneous squamous cell carcinoma (SCC) is a common cancer in white populations and its disease burden is often substantially underestimated. SCC occurs more often in men than women and increases dramatically with age; those affected often develop multiple primaries over time, which increases the burden. The main external cause is solar ultraviolet radiation (UVR), with immunosuppression being the other established risk factor, shown by the high SCC rates in organ transplant recipients. Sunbed use and certain genetic disorders and medical conditions are also associated with SCC, while associations with human papillomavirus infection and high bodyweight are not established. The presence of actinic keratoses (AKs) on sun‐damaged skin is one of the strongest predictors of SCC in unaffected people and a very small proportion of AKs are SCC precursors, although the true rate of malignant transformation of AKs is unknown. The mainstay of SCC prevention is protection of the skin from undue sun exposure by use of clothing cover and sunscreen during summer or in sunny places. Educational, behavioural and multicomponent interventions directed at individuals ranging from parents of newborns, to school children and adolescents, to outdoor workers, have repeatedly been shown to be effective in improving sun‐protective behaviours. Health policies can facilitate SCC prevention by setting standards for relevant behaviours to reduce UVR exposure, for example, by legislated restriction of the tanning industry. Skin cancer prevention initiatives are generally highly cost‐effective and public investment should be encouraged to control the growing public health problems caused by SCC.